Penghapusan Pembantu Pegawai Pencatat Nikah (P3N) Terhadap Pelayanan Pernikahan - Siregar, Adelina; Nasution, Muhammad Arsad; Sainul, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study examines the impact of removing P3N on marriage services at the Padang Sidempuan city Office of Religious Affairs after the fall of the instruction of the Directorate General of Islamic Community Guidance number Dj.II/113 of 2009 regarding the use PNBP funds for marital reconciliation and P3N management, as well as the instruction of the Director General of Islamic Community Guidance number Dj.II/1 0f 2015 about the P3N designation for regions D1 and D2. The research method used is field research with a qualitative approach.The primary data from the instruction of the Directorate General of Islamic Community Guidance number Dj.II/113 of 2009, instruction of the Director General of Islamic Community Guidance number Dj.II/1 0f 2015, Head of KUA Padangsidimpuan Selatan district, Padangsidimpuan Tenggara district, the Padangsidimpuan Angkola Julu district, P3N who was dismissed and the community. And the secondary data in this study are books, journals, theses and other supporting sources.Data collection techniques with observation, interviews, and documentation, with qualitative descriftive data analysis techniques. As for the reserach results obtained in this study P3N removal is carried out in two stages, namely 1) all P3N in the working area of KUA Padangsidimpuan city were officially abolished since the fall of intruction of the Director General of Islamic Community Guidance number Dj.II/113 of 2009 and 2) was not reappointed after an instruction from the Director General of Islamic Community Guidance number Dj.II/I of 2015 because the entire area of KUA Padangsidimpuan city is classified as typology C. 1) The impact of removing P3N is that it has an impact on KUA which has one who doubles as the head of KUA. 2)There was a time conflict between someone who wanted to consult with the time of registration of marriage outside the KUA. 3) Information that is slow to reach the public. 4) Wedding schedule shift. 5)P3N is still used by the public.